Efficient visible photoinitiator with high‐spectrum stability in an acid medium for free‐radical and free‐radical‐promoted cationic photopolymerization based on erythrosine B derivatives. Issue 10 (20th November 2015) - Nan, Xuying; Huang, Yi; Fan, Qinguo; Shao, Jianzhong; Yao, Yuhua
ABSTRACT: Three dye‐linked photoinitiators with excellent spectral stability in an acid medium were synthesized by the covalent bonding of a coinitiator (tertiary amine) and a benzoyl group or two coinitiators to the phenolic and carboxyl group position of erythrosine B. The combination of the iodonium salt and free tertiary amino used to initiate the free‐radical/cationic visible photopolymerization was investigated to acquire the relationship between the structure and performance. The photoinitiating ability of the derivative with the phenolic position bearing a coinitiator was poorer than of the derivative with the carboxyl group bearing one because of the strong back electron transfer of the former. For the derivative with a linked coinitiator on the carboxyl position, the proximity effect between the sensitizer and the coinitiator moiety resulted in an excellent photoinitiating ability for radical/cationic polymerization; this suggested its potential for application. Although radical/cationic photopolymerization could be initiated by the derivative/coinitiator/iodonium salt, the different component ratios between them had different effects on these two polymerizations; this provided useful information for the design of effective photoinitiators for different polymerizations. On the basis of the fluorescence quenching and photopolymerization results, a corresponding synergistic mechanism was proposed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43035. Abstract :